Study on Mud Management West Banko Area at PT. Bukit Asam - Andrew; Chandra , Bogireddy (Indonesian Journal of Environment and Sustainability Issues, 2025)
This study investigates mud management in the West Banko area at PT Bukit Asam, focusing on predicting erosion rates, estimating mud volumes, and evaluating sediment pond (KPL) capacity. The methodology integrates field data collection (rainfall, runoff, and soil properties), the Universal Soil Loss Equation (USLE) approach—considering rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), and cover-management (C)—and sediment delivery ratio (SDR) analysis to estimate sediment yield. Results indicate that the predicted annual erosion rate reached 10,818,825.04 m³/year in Pit SJS, 3,190,396.61 m³/year in Pit E, and 1,642,899.98 m³/year in Pit 3 East. After applying SDR values, the corresponding estimated mud (sediment yield) volumes were 3,129,918.88 m³/year (Pit SJS), 971,015.11 m³/year (Pit E), and 500,266.05 m³/year (Pit 3 East). These findings highlight the significant sediment load generated by mining activities, requiring large-capacity sediment ponds to maintain sump functionality and prevent pump inefficiency. The scientific contribution of this study lies in providing a comprehensive quantitative framework for predicting erosion and sediment yield in dynamic open-pit mining environments. By combining hydrological, soil, and slope factors into an integrated mud management system, the research enhances environmental engineering practices by supporting optimized sump design, sediment pond planning, and sustainable water management strategies. Overall, effective mud management not only ensures operational efficiency and slope stability but also minimizes environmental risks, aligning coal mining operations with good mining practices and regulatory compliance.